Asymmetric ketone reduction by immobilized Rhodotorula mucilaginosa - Liu, Hui (2018)
In our previous study, Rhodotorula mucilaginosa (R. mucilaginosa) was selected via high throughput screening as a very active and selective whole-cell biocatalyst for the asymmetric reduction of ketones. In this study, the reduction of ketones to the desired chiral alcohols by immobilized cells of this strain was investigated. Characterization with Fourier-transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) showed that whole R. mucilaginosa cells were successfully immobilized on support matrices composed of agar, calcium alginate, PVA-alginate and chitosan. The immobilized cells were applied to the enantioselective reduction of fourteen different aromatic ketones. Good to excellent results were achieved with R. mucilaginosa cells immobilized on agar and calcium alginate. The immobilized cells on the selected support matrix composed of agar exhibited a significant increase in pH tolerance at pH 3.5-9 and demonstrated highly improved thermal stability compared to free cells. The cells immobilized on agar retained 90% activity after 60 days storage at 4 ° C and retained almost 100% activity after 6 reuse cycles. In addition, the immobilization procedures are very simple and cause minimal pollution. These results suggest that the application of immobilized R. mucilaginosa can be practical on an industrial scale to produce chiral alcohols.